PENGGUNAAN SIMULASI KOMPUTER UNTUK OPTIMALISASI KEBUTUHAN ALAT BERAT PEKERJAAN PEMINDAHAN TANAH - Arief Setiawan Budi Nugroho; Akhmad Aminullah (Rekayasa Sipil, 2021)
Earthmoving work is often performed based on simple calculation and experience. This practice may work on a small project. However, for a big project in which a large excavation volume must be accomplished, managing the work become more complex. Some different equipment in various types and sizes need to be assigned. Project managers should determine the best combination of equipment with the correct amount to achieve a satisfactory result. This research was conducted to optimize the productivity-cost index in earthmoving works using a discrete event simulation (DES) analysis in four different schemes. An underpass project in Yogyakarta was used as the case study. The optimal combination of equipment was determined by the highest value of the productivity-cost index. The result shows that the highest productivity-cost index of 18.22 was achieved by the combination of four big excavators and 90 small trucks (2E4 90D1). It offered a better productivity-cost index compare to the contractor’s existing equipment combination which could only reach a productivity-cost index of 5.3.